Equivalence between the semiclassical and effective approaches to gravity - Paszko, Ricardo; Accioly, Antonio Jose [UNESP] (Iop Publishing Ltd, 2010)
Semiclassical and effective theories of gravitation are quite distinct from each other as far as the approximation scheme employed is concerned. In fact, while in the semiclassical approach gravity is a classical field and the particles and/or remaining fields are quantized, in the effective approach everything is quantized, including gravity, but the Feynman amplitude is expanded in terms of the momentum exchanged between the particles and/or fields. In this paper, we show that these approaches, despite being radically different, lead to equivalent results if one of the masses under consideration is much greater than all the other energies involved.